PELANGGARAN PRINSIP KERJA SAMA KOMUNIKASI DI LAMAN GRUP FACEBOOK “VIKTOR LERIK BEBAS BERBICARA” - Lian, Yohanes Pemandi; Langkelang Niron, Yakobus M. (Jurnal Lazuardi, 2024)
The principle of cooperation (maxim) is one of the discourses in pragmatic studies that explores the concept of communication between speakers and speech partners. A cooperative process in understanding meaning is needed to achieve communication goals. This research uses Grice's thinking in examining speech act violations, namely violations of the maxim of cooperation on the Viktor Lerik Bebas Berbicara facebook group page. The aim is to describe forms of violation of the maxim of cooperation in conversations contained in the Viktor Lerik Bebas Berbicara facebook group. The theoretical studies used in this research are speech acts, written language on social media, Grice's maxim of cooperation. This research uses a qualitative approach with descriptive methods. The results of the research found violations of the maxim of cooperation, namely violations of the maxim of quantity, violations of the maxim of quality, violations of the maxim of relevance, and violations of the maxim of implementation/manner. The dominant violation that appears is the violation of the maxim of relevance.